2016
DOI: 10.4081/aiua.2015.4.265
|View full text |Cite
|
Sign up to set email alerts
|

The comparative evaluation of apoptosis produced by leuprolide or orchiectomy on rat prostate tissue

Abstract: If the aim of treatment in androgen dependent prostatic adenocarcinoma or benign prostate hypertrophy is the construction of a robust apoptosis, bilateral orchiectomy generates a more powerful apoptosis compared with Leuprolide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Orchidectomy and treatment with GnRH agonists such as leuprolide are successful interventions for prostate cancer by initiating testosterone deficiency [ 27 ], although orchidectomy is more effective for the initiation of glandular apoptosis and atrophy [ 28 ]. Testosterone deficiency produces complications including increased central obesity, increased triglycerides concentrations and elevated fasting plasma glucose concentrations [ 10 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orchidectomy and treatment with GnRH agonists such as leuprolide are successful interventions for prostate cancer by initiating testosterone deficiency [ 27 ], although orchidectomy is more effective for the initiation of glandular apoptosis and atrophy [ 28 ]. Testosterone deficiency produces complications including increased central obesity, increased triglycerides concentrations and elevated fasting plasma glucose concentrations [ 10 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in rats have shown that situations of androgenic reduction such as castration, diabetes, and obesity can alter the histology of the prostate, causing atrophy of the epithelium and luminal enlargment [24,25]. Therefore, we suggest that an excessively hyperlipidic diet also has an atrophic effect on mice prostate and possibly may interfere with the reproductive function of the gland.…”
Section: Discussionmentioning
confidence: 73%